TINGKAT KOMPETENSI ANDRAGOGIK LULUSAN PROGRAM STUDI S1 AGRIBISNIS UNIVERSITAS TERBUKA - Nurul Huda (Jurnal Pendidikan, 2010)
Agricultural extension workers must have several competencies in order to do their job properly.One essential competence to master was related to their andragogic abilities, especially in mastering the concepts of extension and adult education.This research was intended to identify the andragogic competence of agricultural extension workers graduated from Universitas Terbuka (UT). The information of competence aspects such as knowledge, affective, and psychomotor were also collected to elaborate the findings. By using an explanatory research design, a survey technique was implemented among 111 agricultural extension workers who were graduated from UT in four different locations, namely Serang, Karawang, Cirebon, and Tanggamus. Data were collected by using questionnaire and analyzed by using descriptive statistics. In depth interview was also conducted to elaborate the findings. The findings indicated that agricultural extension workers graduated from UT generally had a medium level in their andragogic competence, either in implementing the concepts of extention or in adult education. Their level of knowledge and psychomotor was low, while their affective level were moderate.